Studi Komparatif Dan Kontrastif Nilai-Nilai Fonologi Antara Bahasa Indonesia Dan Bahasa Arab Bagi Mahasiswa Program Studi Pendidikan Bahasa Arab UIN Sunan Ampel Surabaya - Muflihah Mufilhah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2017)
Phonology (‘Ilmu A?wat) is a branch of linguistics that talks about the sound of language that is able to distinguish the meaning of a word or a science that studies the sounds of particular language according to its function to distinguish lexical meaning. The first problem in learing oral language is the problem of his speech. Before someone learns the meaning of various words and grammar, he must recognize the sounds used in that language. Therefore, the researcher proposes the title to find out some of the problems examined in this study: how to compare the phonological values between Arabic and Indonesian language in order to develop teaching materials for a?wat sciense materials to identify these problems in depth and comprehensively. This research uses qualitaive-descriptive. The results of this study are a comparative study of phonological values between Arabic and Indonesian is the possibility of identical characteristics between both of them in term of places of articulation and the sound charasteristics.